Aplikasi Asuransi Kesehatan Pada Mahasiswa Keperawatan - Zia Ul Haq; Lailatul Kodriyah; Ida Herawati; Ronal Surya Aditya (Jurnal Keperawatan, 2021)
Health insurance from the government, known as Askes, was renamed BPJS. One of the residents of Indonesia are students who take part in the program. The purpose of this study was to determine the experience of students becoming users of health insurance. Method This research is a qualitative research with a descriptive phenomenological design, data obtained through in-depth interviews. Stages of analysis Data obtained by in-depth interviews can be analyzed the process of data analysis with Interpretative Phenomenological Analysis (IPA). The study population was 15 nursing student respondents. The results showed that there were 8 themes: 1) Health Insurance Services 2) Welfare 3) Hospital Costs 4) Social Health Insurance 5) Economic Problems 6) Time 7) Increase 8) Pain. The conclusion of this study is that students consider that current health services were not good, for example long waiting times and health insurance have an influence on welfare and the economy.